An event-related potential study on the time course of mental rotation in upper-limb amputees. Issue 5 (May 2017) - Lyu, Yuanyuan; Guo, Xiaoli; Bekrater-Bodmann, Robin; Flor, Herta; Tong, Shanbao
Highlights: Amputees and controls showed a comparable P100 during early visual processing phase of a mental hand rotation task. Amputees exhibited a reduced N200 in the categorization of hand stimuli, and this abnormality was correlated with the duration since amputation. Amputees had a larger P300 for the intact upright hand in the mental rotation phase, indicating that the intact hand gained more significance. Abstract: Objective: Mental rotation of body parts involves sequential cognitive processes, including visual processing, categorization and the mental rotation process itself. However, how these processes are affected by the amputation of a limb is still unclear. Methods: Twenty-five right upper-limb amputees and the same number of matched healthy controls participated in a hand mental rotation task. Thirty-two-channel electroencephalography (EEG) was recorded and the event-related potentials (ERPs) were analyzed. Results: In the early visual processing phase, amputees and controls showed a similar P100. During the categorization phase, the amputees exhibited a decreased N200 compared with controls, and the decline was positively correlated with the time since amputation. In the mental rotation phase, controls had a larger ERP for the right upright hand than for the left upright hand, while amputees had a larger ERP for the left (intact) upright hand than for the right (affected) upright hand. Conclusions: Early visual processing was not affected by limb amputation. However, the perceptual salience of hand pictures decreased and the intact hand gained more significance in the amputees. Significance: Event-related potentials had the capability of showing the differences in categorization and mental rotation phases between amputees and controls.